Education, medical care and treatment of women with various forms of high blood pressure during pregnancy - Mężyk, Izabela; Kotlarz, Barbara; Naworska, Beata; Gogola, Celina; Gałązka, Iwona; Podsiadło, Beata (Nursing Problems / Problemy Pielęgniarstwa, 2010)
Hypertension is one of the most common pathology in pregnancy and factors of maternal mortality in developed countries, as well as the source of many complications in children. Despite a significant progress in knowledge of etiopathology and treatment of high blood pressure during pregnancy the only causal treatment of preeclampsia is by induction of the labour of a child and placenta. Knowledge and experience of medical staff is of importance to achieve intended aims in treatment and care of hypertensive pregnant women; however, patient’s cooperation and an aware approach towards treatment is also essential. Nursing Topics 2010; 18 (4): 512-517